The number of the CTCF binding sites of the H19/IGF2:IG-DMR correlates with DNA methylation and expression imprinting in a humanized mouse model. Issue 16 (5th May 2021) - Freschi, Andrea; Del Prete, Rosita; Pignata, Laura; Cecere, Francesco; Manfrevola, Francesco; Mattia, Monica; Cobellis, Gilda; Sparago, Angela; Bartolomei, Marisa S; Riccio, Andrea; Cerrato, Flavia
Abstract: The reciprocal parent of origin-specific expression of H19 and IGF2 is controlled by the H19/IGF2 :IG-DMR (IC1), whose maternal allele is unmethylated and acts as a CTCF-dependent insulator. In humans, internal IC1 deletions are associated with Beckwith–Wiedemann syndrome (BWS) and Silver-Russell syndrome (SRS), depending on their parental origin. These genetic mutations result in aberrant DNA methylation, deregulation of IGF2 / H19 and disease with incomplete penetrance. However, the mechanism linking the microdeletions to altered molecular and clinical phenotypes remains unclear. To address this issue, we have previously generated and characterized two knock-in mouse lines with the human wild-type (hIC1wt) or mutant (hIC1∆2.2) IC1 allele replacing the endogenous mouse IC1 (mIC1). Here, we report an additional knock-in line carrying a mutant hIC1 allele with an internal 1.8 kb deletion (hIC1∆1.8). The phenotype of these mice is different from that of the hIC1∆2.2-carrying mice, partially resembling hIC1wt animals. Indeed, proper H19 and Igf2 imprinting and normal growth phenotype were evident in the mice with maternal transmission of hIC1Δ1.8, while low DNA methylation and non-viable phenotype characterize its paternal transmission. In contrast to hIC1wt, E15.5 embryos that paternally inherit hIC1Δ1.8 displayed variegated hIC1 methylation. In addition, increased Igf2 expression, correlating with increased body weight, was found in one third of these mice. Chromatin immunoprecipitation experiments in mouse embryonic stem cells carrying the three different hIC1 alleles demonstrate that the number of CTCF target sites influences its binding to hIC1, indicating that in the mouse, CTCF binding is key to determining hIC1 methylation and Igf2 expression.